2021
DOI: 10.3390/brainsci11060766
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Learning through Action Observation: Preliminary Evidence from Virtual Gardening Activity in Intellectual Disability

Abstract: Intellectual disability (ID) compromises intellectual and adaptive functioning. People with an ID show difficulty with procedural skills, with loss of autonomy in daily life. From an embodiment perspective, observation of action promotes motor skill learning. Among promising technologies, virtual reality (VR) offers the possibility of engaging the sensorimotor system, thus, improving cognitive functions and adaptive capacities. Indeed, VR can be used as sensorimotor feedback, which enhances procedural learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…One study used VR to train community-dwelling adults how to wire an electrical outlet in their vocational assistance center or at home ( 33 ), while another study used AR as a task prompting system to aid job coaches in training food preparation for community-based supported employment service users with ID ( 7 ). Lastly, semi-immersive VR scenarios were used to teach adults with ID in a residential home the work task of sowing zucchini seeds ( 31 ). These three studies reported that participants were able to learn the specific tasks well, although no validated measurements were used ( 7 , 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used VR to train community-dwelling adults how to wire an electrical outlet in their vocational assistance center or at home ( 33 ), while another study used AR as a task prompting system to aid job coaches in training food preparation for community-based supported employment service users with ID ( 7 ). Lastly, semi-immersive VR scenarios were used to teach adults with ID in a residential home the work task of sowing zucchini seeds ( 31 ). These three studies reported that participants were able to learn the specific tasks well, although no validated measurements were used ( 7 , 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lastly, semi-immersive VR scenarios were used to teach adults with ID in a residential home the work task of sowing zucchini seeds ( 31 ). These three studies reported that participants were able to learn the specific tasks well, although no validated measurements were used ( 7 , 31 , 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite this limited space, our work process was analogous to others in terms of where open VR environments were constructed. An example of this is the interactive mapping approach to explore open urban landscapes by Edler et al [86] or the work of Giachero et al [87] on virtual gardening and intellectual disability.…”
Section: Discussionmentioning
confidence: 99%